Experiential knowledge of expert coaches and expert athletes can help identify constraints on the performance of run-up in competitive sport tasks - Ghorbanzadeh, Behrouz; Mohammadi Orangi, Behzad; Yaali, Rasoul (Frontiers in Psychology, 2025)
IntroductionUnderstanding athletes’ performance in competitive environments helps practitioners design practice environments to improve athletes’ skills. This study investigated the experiential knowledge of 30 elite coaches and athletes from track and field, gymnastics, and soccer, aimed at increasing understanding of individual, environmental, and task constraints on expert athletes’ performance.MethodsThe interviews were conducted in a semi-structured manner and based on ecological dynamics.ResultsResults show that while some constraints on run-up performance are common across all three sports, others are sport-specific. Focus, readiness, self-confidence, speed, and decision-making were identified as individual constraints. Environmental constraints included spectators, coach role, practice facilities, and competition stakes. Task constraints comprised performance order, markers, significant others in the competition, and competition timing and results.DiscussionThe findings support the ecological dynamics perspective that athlete performance emerges from the interaction of environmental, task, and personal constraints. Athletes must maintain focus during run-up while managing various pressures, including crowd noise and competition stress. Coaches provide crucial technical and psychological support that enhances confidence and focus. Quality practice facilities and consistent training environments aid athletes’ spatial awareness and situational resilience. Task-specific constraints, such as performance order and timing, present unique challenges that athletes must navigate through dynamic adjustments based on real-time changes in conditions. The results contribute to the design of training environments and consequently to athletes’ performance improvement. The study suggests that coaches should design training environments that simulate real-world competitive constraints to help athletes develop adaptive skills under pressure. These findings have practical implications for designing training programs that enhance athletes’ ability to perform consistently in high-stakes competitive situations.